The Prevalence of Coxiella burnetii in Hard Ticks in Europe and Their Role in Q Fever Transmission Revisited—A Systematic Review - Körner, Sophia; Makert, Gustavo R.; Ulbert, Sebastian; Pfeffer, Martin; Mertens-Scholz, Katja (Frontiers in Veterinary Science, 2021)
The zoonosis Q fever is caused by the obligate intracellular bacterium Coxiella burnetii. Besides the main transmission route via inhalation of contaminated aerosols, ticks are discussed as vectors since the first isolation of the pathogen from a Dermacentor andersonii tick. The rare detection of C. burnetii in ticks and the difficult differentiation of C. burnetii from Coxiella-like endosymbionts (CLE) is questioning the relevance of ticks in the epidemiology of Q fever. In this review, literature databases were systematically searched for recent prevalence studies concerning C. burnetii in ticks in Europe and experimental studies evaluating the vector competence of tick species. A total of 72 prevalence studies were included and evaluated regarding DNA detection methods and collection methods, country, and tested tick species. Specimens of over 25 different tick species were collected in 23 European countries. Overall, an average prevalence of 4.8% was determined. However, in half of the studies no Coxiella-DNA was detected. In Southern European countries a significantly higher prevalence was observed, possibly related to the abundance of different tick species here, namely Hyalomma spp. and Rhipicephalus spp. While a similar proportion of studies used ticks sampled by flagging and dragging or tick collection from animals, under 30% of the total tick samples derived from the latter. There was no significant difference in the various target genes used for the molecular test. In most of the studies, no distinction was made between C. burnetii and CLE. The application of specific detection methods and the confirmation of positive results is crucial to determine the role of ticks in Q fever transmission. Only two studies were available, which assessed the vector competence of ticks for C. burnetii in the last 20 years, demonstrating the need for further research.